Correlation of dynamic contrast‐enhanced MRI derived volume transfer constant with histological angiogenic markers in high‐grade gliomas. Issue 4 (13th January 2018) - Di, Ningning; Yao, Chenjun; Cheng, Wenna; Ren, Yan; Qu, Jianxun; Wang, Bin; Yao, Zhenwei
Abstract: Introduction: To ascertain if the volume transfer constant ( K trans ) derived from T1 dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI) correlates with the immunohistological markers of angiogenesis in high‐grade gliomas. Methods: Fifty‐one image‐guided biopsy specimens in 34 patients with newly presenting high‐grade gliomas (grade III = 16; grade IV = 18) underwent preoperative imaging (conventional imaging and T1 DCE‐MRI). We correlated vascular endothelial growth factor (VEGF) expression and the microvessel density (MVD) of MRI‐guided biopsy specimens with the corresponding DCE‐derived K trans . Histological sections were stained with VEGF and CD34, and examined under light microscopy. These histological and molecular markers of angiogenesis were correlated with the K trans of the region of interest corresponding to the biopsy specimen. Results: The K trans showed a significant positive correlation with VEGF expression ( ρ = 0.582, P = 0.001) but not with MVD stained with CD34 antibody ( ρ = 0.328, P = 0.072). Conclusion: The K trans derived from DCE‐MRI can reflect the VEGF expression of high‐grade gliomas but not the MVD.